Hubungan Keterlibatan Orang Tua dengan Prestasi Belajar Matematika Siswa Kelas IV SD Inpres 18 Kabupaten Sorong - Glory Gracia Christadella; Mursalim Mursalim; Dwi Pamungkas (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study aimed to determine the relationship between parental involvement and mathematics learning achievement of fourth-grade students at SD Inpres 18 Sorong Regency. The research employed a quantitative approach with a correlational design. The research subjects consisted of all fourth-grade students from classes IV A and IV B, totaling 66 students. Data on parental involvement were collected using a questionnaire, while students’ mathematics achievement data were obtained from documentation of end-of-semester promotion examination scores. Data analysis was conducted using descriptive and inferential statistics. The prerequisite tests included the Kolmogorov–Smirnov normality test with a Monte Carlo approach and a linearity test. Hypothesis testing was carried out using Pearson Product Moment correlation with the assistance of SPSS software. The results showed a positive and significant relationship between parental involvement and students’ mathematics achievement, with a correlation coefficient of r = 0.637 and a significance value of p = 0.000 (p < 0.05). This correlation is categorized as strong. The findings indicate that higher levels of parental involvement in guiding, supervising, and providing emotional support are associated with higher mathematics learning achievement among students. Therefore, parental involvement plays an important role in supporting the mathematics learning success of elementary school students.